A Case Study of Cognitive Behavioral Therapy for a Case of Depression - Mustafa Muammar Habil (Journal of Scientific and Human Dimensions, 2026)
This study demonstrates the importance and effectiveness of cognitive-behavioral strategies in treating a case of severe depression. It is divided into two parts: the first part is the theoretical section, which includes concepts related to the case study, such as the definition of depression and the definition of cognitive-behavioral therapy.The second part comprises the practical application, presenting the methodological aspects, the case study, functional analysis, hypotheses, and treatment strategies (the outcome of the therapy sessions). The study concludes with a summary and conclusions.
Keywords: Effectiveness; Cognitive-Behavioral; Severe Depression; Case Study; Therapy